Rare Earth Complexes with Benzil-α-dioxime - Patil, B.K.; Deshpande, N.; Deshpande, N. (Asian Journal of Chemistry, 2010)
Simple complexes of Y(III), Ce(IV), La(III), Pr(III), ND(III), Sm(III), Gd(III) using benzil-α-dioxime (diphenyl-glyoxime) have synthesised. These complexes have been characterised by a study of elemental analysis, conductivity and infra-red spectra. Physical properties and analytical data of the complexes reveal that each metal ion is attached to one molecule of the ligand. The presence of coordinated water molecules in all the complexes may be confirmed by thermal study and from infra-red spectral studies of the complexes. The conductivity data obtained in the solvents ethanol and methanol indicate that all the complexes are 1 : 1 electolytes. Hence one can assign the general formula [LnLCl22H2O]Cl where Ln ═ Y, Ce, La, Pr, Nd, Sm, Gd and L is benzil-dioxime. It can be said that the coordination number in these complexes is six.